The kidnapping of the chibok girls: a result of a threat to masculinities - Silverio Torres, Néstor Guillermo (2017)
On April 14th, 2014, Boko Haram seized a Governmental School in Chibok, abducting 276 girls to force them to convert to Islam. These events have thus been examined in accordance to International Security and Governmental perspectives. This bachelor dissertation proposes to analyze the response of this extremist group to girl education taking as an example the kidnapping aforementioned. Following an African Feminist approach, the researcher explores the gender constructions of the extremists in regard to what they deem to be masculine, and how women empowerment is a threat to their identity. For this reason, an explorative methodology is used within a post-colonial approach. This avoids generalizations and ill-fitting explanations of the subject of study, focusing primarily on its understanding. Furthermore, before addressing the Chibok abductions, this research refers to the international and local context that led to the appearance of Boko Haram, emphasizing in the contrasting relation between Westernized globalization and a regional fundamentalist revival. Following these arguments, this Dissertation considers the socio-political background of the Federal Republic of Nigeria, centering on the structure in the Northern states, which perpetuates patriarchal traditions. Likewise, this analysis is completed by an exploration on how masculinity is constructed in a binary perspective, that is in terms of the other. In addition, the student contemplates if these Nigerian militants would be experiencing a Hegemonic Masculinity crisis, a phenomenon that accentuates gender-based violence if male privilege is contested. Finally, this investigation ends with an additional examination of the possibility of an educational system that empowers both girls and boys against toxic gender constructions